2015
DOI: 10.1111/1556-4029.12859
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of High‐throughput Metagenomic Sequencing of Aquatic Bacterial Communities to Estimate the Postmortem Submersion Interval

Abstract: Human remains can be discovered in freshwater or marine ecosystems, circumstances where insects and other invertebrates have infrequently been used for understanding the time of postmortem submersion. In this study, the identification and succession of epinecrotic bacterial communities on vertebrate remains were described during decomposition in a temperate headwater stream during two seasons (summer and winter). Bacterial communities were characterized with 454 pyrosequencing and analyzed at phyletic and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 103 publications
(143 reference statements)
13
89
1
Order By: Relevance
“…Although the dominant bacterial community diversity at the phyla level showed no evident uctuation, we found that changes in the phyla Firmicutes and Proteobacteria were in the opposite direction of the relative abundance over time, which was consistent with a previous study [27]. Previous research aiming at the epinecrotic communities on human corpses showed that Firmicutes formed the inherent phylum for corpses, while Proteobacteria was initially identi ed from the environment, and the reason for the increase in Proteobacteria was outer bacterial migration [28][29][30]. This suggests that the increased relative abundance of Proteobacteria in the rectum of dead rats after 8 h may be due to the migration from the external environment.…”
Section: Discussionsupporting
confidence: 93%
“…Although the dominant bacterial community diversity at the phyla level showed no evident uctuation, we found that changes in the phyla Firmicutes and Proteobacteria were in the opposite direction of the relative abundance over time, which was consistent with a previous study [27]. Previous research aiming at the epinecrotic communities on human corpses showed that Firmicutes formed the inherent phylum for corpses, while Proteobacteria was initially identi ed from the environment, and the reason for the increase in Proteobacteria was outer bacterial migration [28][29][30]. This suggests that the increased relative abundance of Proteobacteria in the rectum of dead rats after 8 h may be due to the migration from the external environment.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to vertebrate decomposition in terrestrial systems (e.g [12]. ), early decomposer communities were dominated by bacteria in the phylum Proteobacteria and later decomposer communities were dominated by bacteria in the phylum Firmicutes [34]. Postmortem taxa appeared to be a mix of mammal-associated and water-associated organisms [34].…”
Section: Which Environmental Variables Need To Be Included In Microbimentioning
confidence: 95%
“…Another major knowledge gap is how different environments such as terrestrial, aquatic, and indoor/built environments affect the succession of microbes during mammalian decomposition. In a study of swine decomposition in freshwater, Benbow et al [34] discovered a similar succession of microbes across individuals in two seasons. Similar to vertebrate decomposition in terrestrial systems (e.g [12].…”
Section: Which Environmental Variables Need To Be Included In Microbimentioning
confidence: 98%
“…The typical decomposition process in aquatic environments may be affected by both environmental factors and factors related to the body itself. Environmental factors include, but are not limited to, water temperature, salinity, water depth, current flow, the season of submergence, availability of the body to macro and micro scavengers, water chemistry, and aquatic microbiome (4,(11)(12)(13)(18)(19)(20).…”
Section: Accepted Manuscriptmentioning
confidence: 99%